Necessary Conditions for Optimal Control Problems with Infinite Horizons - Halkin, Hubert (Econometrica, 1974)
Abstract : In a classical optimal control problem the terminal time, either prescribed a priori or not, is always a real number. In many dynamic optimization problems in economics one is lead to consider optimal control problems in which the terminal time is the extended real number + infinity. These are the so called optimal control problems with infinite horizon. In the paper the author gives a precise formulation for a standard problem of that type and establishes a necessary condition for that problem. (Author)